Pendampingan Masyarakat Desa Kenongo dalam Peningkatan E-Business di Kabupaten Sidoarjo - Fitri Nur Latifah; Imam Fauji; Diah Krisnaningsih (LPPM Universitas Yudharta Pasuruan, 2020)
Today's technological developments have eliminated limitations and opened up various business opportunities that are assisted by the internet which is commonly called e-business. In e-business activities there are several positive and negative impacts. If seen from real activities, there are many positive impacts mentioned that are able to improve the performance of SME, facilitate business access, be more effective and efficient in daily economic activities. The negative impact that is often encountered in the field is prone to fraud and raises concerns in the community will make the business offline or the market will close down. This program aims to provide literacy to the public about sharia e-business and also socialization on how to apply e business properly and wisely to avoid negative impacts. This program will provide literacy in the form of modules on e-business as well as socialization and assistance to SME and Kenongo villagers, especially housewives, whether they have businesses or not. It is hoped that Kenongo villagers will be able to have a good and wise understanding in applying e business in daily economic life as well as avoiding the negative impacts of e-business. So that through e-business can be an economic empowerment of citizens